Critical Parts. Die Umsetzung des neuen Sicherheitskonzepts am Flughafen Frankfurt. - Müller, Markus; Schöntag, Ina (Deutscher Verkehrs-Verl., 2007)
Mit dem Inkrafttreten der EU-Luftsicherheitsverordnung im Jahr 2003 wurden die Sicherheitsbestimmungen an europäischen Flughäfen deutlich verschärft. Für die Fraport AG als Betreiber des Flughafens Frankfurt bedeutete dies, umfassende Umbaumaßnahmen zu planen und in das Flughafensystem zu integrieren, um die Sicherheit an Deutschlands größtem Flughafen - an den neuen Anforderungen orientiert - zu gewährleisten. difu

Security concerns in air transport - and therefore at Frankfurt Airport - have always been a top priority. Before 11 September 2001, all persons wishing to enter areas of top security at Frankfurt airport needed a special entry permit (Flughafenausweis) that was only issued after prior verification of trustworthiness, covering a check of the person's identity and his or her authorization. In the wake of the events of 11 September 2001, regulations concerning civil air transport security measures have been considerably expanded by the EU. As of 1 January 2006, Fraport AG has stipulated that air terminals and aprons make up the airport's "security sensitive" areas. All persons wishing to enter the apron area have been subject to special security checks - together with their carry-on items and accompanying vehicles - at pedestrian and road entry points with the help of modern access control devices and screening techniques. difu
Keywords: Öffentlicher Verkehr; Luftverkehr; Flughafen; Umbau; Sicherheitskonzept; Verordnung; Zugangskontrolle; Luftsicherheit; EU-Verordnung; Sicherheitsmanagement